Go to bed! kids and sleep - Learning seed; Stage Fright Production (Lake Zurich, Ill. : Learning Seed, 2006)
Explain children sleeping behavior start with babies until the teenager. Its discusses the Circadian rhythm, what does a baby's brain do while sleep, how baby apperas in the different phases of sleep, what does program suggest parents to do help their babies asleep, discuss the sleep needs of the school age child and so on.
Writer and executive producer, Louise Welsh Schrank
Voice over : Anne Gallagher
Keywords: Children -- sleep; Bedtime; Sleep; Infant -- Sleep